Principal’s Managerial Conceptual Skills and Teachers Job Performance in Secondary Schools in Nigeria - Ukozor, Conrad Ugochukwu; Edet, Inemesit Nsikak (Jurnal Pendidikan Non formal, 2024)
This paper is a review study that examines the impact of principals’ managerial conceptual skills on teacher’s job performance in secondary schools in Nigeria and beyond. Secondary data were used in the paper. The data were sourced from print and online publications. The result collected revealed that 83% agreed principal’s managerial conceptual skills have an impact on teachers’ job performance in secondary schools. Based on the findings of this study, the following recommendations were made that the government should design training programmes for school principals on how to apply the appropriate managerial styles and skills in every situation that arises in school administration. Principals should supervise, guide and help teachers to improve their professional skills by supporting the teachers and providing necessary resources for them to work.